Response of growing and finishing swine to a dietary source of lactobacillus acidophilus - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
Post-weaning comparisons were made using high and low protein rations with and without a fermentation product (lactobacillus acidophilus). Pigs receiving higher protein rations (18%) grew slightly faster than those receiving low protein (15%) rations; however, the differences were not significant. Adding a fermentation product to either ration tested did not significantly improve performance of weaned pigs. Finishing swine were used to compare high-protein (16%) ration and low-protein (13%) rations with and without the fermentation product. Pigs receiving the higher-protein ration grew significantly faster than those receiving the lower-protein ration with or without the additive. Pigs receiving the additive in the 13% ration grew slightly faster than pigs receiving the 13% ration without the additive.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Growing pigs; Finishing pigs; Lactobacillus acidophilus